Hollywood and war : the film reader - Slocum, J. David (John David) (New York ; London : Routledge, 2006)
Hollywood and War provides analyses of some of the most important productions constituting the war film genre, and pays particular attention to how the constituent elements of that genre emerged and have been continually reproduced and recast from the Spanish-American War, World War I, and World War II, through the Korean War and Vietnam to conflicts in the Gulf and the current war against terrorism. Hollywood and War also discusses the complex institutional relations between Hollywood and the U.S. military, government, and American society.
General Introduction: Seeing Through American War Cinema / J. David Slocum -- Ch. 1. War films / Steve Neale -- Pt. 1. War as a way of seeing -- Ch. 2. War, film, history: American Images of "real war," 1890-1925 / Geoffrey Klingsporn -- Ch. 3. A Travelling Shot over Eighty Years / Paul Virilio -- Ch. 4. Experiences of Modern Warfare and the Crisis of Representation / Bernd Huppauf -- Ch. 5. War as a Way of Seeing / George H. Roeder, Jr. -- Ch. 6. 'Make My Day!': Spectacle as Amnesia in Imperial Politics / Michael Rogin -- Ch. 7. Passions of the Real, Passions of Semblance? / Slavoj Zizek -- Pt. 2. Early Formations of War Cinema in the United States -- Ch. 8. The Spanish-American War in United States Media Culture / James Castonguay -- Ch. 9. The United States Film Industry and World War One / Leslie Midkiff DeBauche -- Ch. 10. War on Film: The American Cinema and World War I, 1914-1941 / Michael Isenberg -- Ch. 11. War and Cinema: Interpreting the Relationship / Pierre Sorlin -- Pt. 3. The Apotheosis of the Hollywood War Film -- Ch. 12. World War II and the Hollywood 'War Film' / Thomas Schatz -- Ch. 13. Leni Reifenstahl's Contribution to the American War Effort / Thomas Doherty -- Ch. 14. Will this Picture Help to Win the War? / Clayton R. Koppes and Gregory D. Black -- Ch. 15. The World War II Combat Film: Definition / Jeanine Basinger. Ch. 16. Hollywood and the World War II Conversion Narrative / Lary May -- Pt. 4. Shadows of ambivalence -- Ch. 17. All Quiet on the Western Front (U.S., 1930): The Antiwar Film and the Modern Image of War? / John Whiteclay Chambers II -- Ch. 18. Missing Action: POW Films, Brainwashing and the Korean War, 1954-1968 / Charles Young. Ch. 19. Film and the War: Representing Vietnam / David E. James -- Ch. 20. Vietnam and the New Militarism / Michael Ryan and Douglas Kellner -- Ch. 21. Race and Nation in Glory / Robert Burgoyne -- Pt. 5. Hollywood and War: Contemporary Formations -- Ch. 22. Techno-Muscularity and the 'Boy Eternal': From the Quagmire to the Gulf / Lynda Boose -- Ch. 23. Seriously Spectacular: 'Authenticity' and 'Art' in the War Epic / Geoff King -- Ch. 24. The Gulf War Did Not Take Place / Jean Baudrillard -- Ch. 25. In the Combat Zone / Marilyn Young -- Ch. 26. A Cultural History of War Without End / Melani McAlister.
Includes bibliographical references and index.